A Low-Noise Amplifier for Submarine Electric Field Signal Based on Chopping Amplification Technology - Fenghai Liu; Shaoheng Chun; Rujun Chen; Chao Xu; Xun Cao (Sensors, 2024)
In the exploration of ocean resources, the submarine electric field signal plays a crucial role through marine electromagnetic methods. However, due to the field signal’s low-frequency and weak characteristics, it often encounters interference from the instrument’s own <semantics>1/f</semantics> noise during its acquisition. To address this issue, we developed a low-noise amplifier for the submarine electric field signal based on chopping amplification technology. This amplifier utilizes low-temperature electronic components to adapt to the cold submarine environment and enhances its independence by incorporating a square wave generator. Additionally, we conducted simulations and experimental tests on the designed chopper amplifier circuit, evaluating the equivalent input voltage noise spectrum (EIVNS) and the frequency response within 1 mHz~100 Hz. The experimental results indicate that the amplifier designed in this study achieves sufficiently low noise 2<semantics> nV/√Hz</semantics>@1 mHz, effectively amplifying the submarine electric field signal measured with the electric field sensor.